Evaluation of muscular functional recovery based on concentration and meditation levels through the use of the computer brain interface - Aiquipa, W.A. (2019)
When we refer to pain, we are faced with an unpleasant sensation that causes certain reactions in the human body that prevent its production, so it is of vital importance to understand what the symptomatology of pain is, how it is produced and how it can be avoided. production, there are cases where the pain becomes pathological where found in the patient's thoughts, therefore the present work tries to demonstrate that its production can be avoided in the face of intense painful situations that occur when working in the recovery of the mobility of the patient. articulation of the knee, which by its nature is painful, added to the fear of feeling pain on the part of the patient does not help the patient's recovery, the experimentation consists of taking the pain from the approach of not thinking about it and relaxing and evaluating it by an environment of cerebral analysis through the levels of attention and meditation, achieved to improve the predisposition of the patient e before the painful situations that were submitted in the development of the rehabilitation exercises, demonstrating that when you do not think about the pain, the levels of meditation increase indicating the absence of pain, consequently the muscles relax and the pain decreases considerably, Otherwise, it happens when the levels of attention are high, indicating that the patient is thinking about pain, feels stressed and identifies the presence of pain on the part of the patient.